(untitled) (Molecular Medicine Communications, 2022)
Change is not easy; it is the nature of human beings to resist change. With COVID-19, people across the world had to completely shift their lifestyles and adapt to an entirely new way of living. Following new rules and new protocols have not been an easy task for everyone and have created newer obstacles for people already suffering from mental health disorders. People have watched their loved ones suffer and surrender to their end. During such times, human connection becomes an important coping mechanism for people. Still, this connection is also lost with social distancing and lockdowns coupled with rising unemployment, fear, and paranoia. As this virus has spread across the world, people are facing another pandemic of depression and anxiety parallel to COVID-19, and it is affecting every single person, whether it’s a doctor, a student, a parent, or a patient suffering from COVID-19. We are all victims of the psychological impacts of the current pandemic. With an alarming increase in mental health, it is imperative that governments across the world pay more attention to the psychological consequences of the pandemic while fighting the virus.